Fêmea-matriz: a maternidade em Ponciá Vicêncio, de Conceição Evaristo - Oliveira, Ana Ximenes Gomes de (2015)
This work aims to analyze the novel Ponciá Vicêncio (2003), by Conceição Evaristo, focusing on maternity as the main analysis category along with its representations on women characters: Ponciá, Maria Vicêncio and Nêngua Kainda. To do so, a study will be done about these characters from the feminine authorship in question, considering the smoldering need of critical-theoretical debate on maternity condition in public and private sphere, based on the feminist criticism view and the cultural studies. It is noticed the necessity discussion about the formation of the women/mother/daughter archetypes that constructs the social and subjective imaginary in patriarchal society, to expose how the feminine and the maternity are presented in the novel, then subvert this oppressive model and deconstruct stereotypes generated in woman-mother-black. In Ponciá Vicêncio, it is observed a representation of maternity and feminine fertility beyond biology that takes shape as a form of feminine resistance and empowerment of its characters. Thus, to clarify this discussion, I use above all, the considerations of Del Priore (2009), Stevens (2007), Badinter (2011) and Nascimento (2008), about maternal condition; Alberti (2004), related to memory and orality; and Prandi (2001) on the representation of mythology of deities in this narrative. Moreover, considering the place of speech occupied by this writer, it is necessary to discuss conceptual issues of the African-Brazilian literature, enjoying the studies of Duarte (2014), as well as the critical clash on post-colonialism and cultural studies from authors as Appiah (1997), Bhabha (2013) and McClintock (2010).